ANALISIS HERMENEUTIK TEKS “NAMUN AKU MENGASIHI YAKUB TETAPI MEMBENCI ESAU” DALAM KITAB MALEAKHI 1:2-5 - Daud Balang; Yusrianto Babuno (Shema: Jurnal Teologi Injili dan Pendidikan Kristen, 2021)
The problem of this research lies in God's expression which says that "I love Jacob but hate Esau" this expression seems to be inversely proportional to the qualities possessed by God himself where God is a loving God, God is just and righteous. This trait is in stark contrast to the expression in Malachi 1:2-3 as if God did not love Esau. This discussion aims to find out the meaning of the sentence I love Jacob but hate Esau in Malachi 1:2-5 and to find out whether this text speaks of the idea of ​​double predestination. So this writing uses a biblical literature research approach. However, the analysis and literature used is taken from various sources to get accurate results. The conclusion of this paper explains that the purpose of God's expression is God showing that the God of the Israelites as proof that God loves Jacob, and God's purpose of hating Esau does not mean "hate" but it means "lack of love". Also in the conclusion of this discussion, it is answered that there is no idea of ​​double predestination but rather the sovereignty of God in choosing people who receive the promise of blessings.